2009
DOI: 10.1002/glia.20911
|View full text |Cite
|
Sign up to set email alerts
|

Structural remodeling of gray matter astrocytes in the neonatal pig brain after hypoxia/ischemia

Abstract: Astrocytes play a vital role in the brain; their structural integrity and sustained function are essential for neuronal viability, especially after injury or insult. In this study, we have examined the response of astrocytes to hypoxia/ischemia (H/I), employing multiple methods (immunohistochemistry, iontophoretic cell injection, Golgi-Kopsch staining, and D-aspartate uptake) in a neonatal pig model of H/I. We have identified morphological changes in cortical gray matter astrocytes in response to H/I. Initial … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
34
0

Year Published

2012
2012
2019
2019

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 31 publications
(36 citation statements)
references
References 56 publications
2
34
0
Order By: Relevance
“…We have demonstrated pre-gliotic astrocyte changes are evident from 1-8h after an HI insult, prior to histological evidence of neuronal damage [6,29]. At 72h post-insult, overall astrocyte size decreased by 30-40% in grey and white matter and these astrocytic changes were associated with histological brain damage [6,28]. Our results and others confirm the importance of neuron-glia interactions in normal brain function [30].…”
Section: Introductionsupporting
confidence: 80%
See 4 more Smart Citations
“…We have demonstrated pre-gliotic astrocyte changes are evident from 1-8h after an HI insult, prior to histological evidence of neuronal damage [6,29]. At 72h post-insult, overall astrocyte size decreased by 30-40% in grey and white matter and these astrocytic changes were associated with histological brain damage [6,28]. Our results and others confirm the importance of neuron-glia interactions in normal brain function [30].…”
Section: Introductionsupporting
confidence: 80%
“…This theory is supported by Martin et al [23] who demonstrated a significant increase in GFAP immunoreactivity in the HI pig brain at 96h post-insult. Our previous studies have demonstrated that the post-HI brain undergoes significant changes in the expression of various astrocytic and neuronal proteins and the structure of grey and white matter astrocytes [6,[24][25][26][27][28][29]. We have demonstrated pre-gliotic astrocyte changes are evident from 1-8h after an HI insult, prior to histological evidence of neuronal damage [6,29].…”
Section: Introductionmentioning
confidence: 90%
See 3 more Smart Citations